Bite-size Python : an introduction to Python programming - Speight, April (Wiley, 2020)
Introduce children to the popular Python programming language through relatable examples and fun projects! Python has now surpassed Java as the most commonly used programming language. As the language rises in popularity, this complete guide can teach basic Python concepts to kids with its simple, friendly format. Bite-Size Python: An Introduction to Python Programming provides children with a foundation in the Python language. This unique book shares knowledge through easy-to-understand examples, fast exercises, and fun projects! As children learn, their parents, caregivers, and instructors can also join in their discoveries. Bite-Size Python is ideal for those who are new to programming, giving kids ages 9 and up a beginners' approach to learning one of the most important programming languages.-Gives an overview of Python -Provides exciting programming projects -Offers instruction on how to download and install Python -Presents key programming language concepts -Simplifies technical definitions With this playful guide to learning Python, readers can try out activities on their computers for a hands-on learning experience. The artwork in Bite-Size Python represents children of various backgrounds, so any child who picks up this book will be empowered to learn and young readers will love showing their projects to friends and family!